Explaining the child poverty outcomes of Japan, South Korea and Taiwan - Bruce Bradbury; Aya Abe; Markus Jäntti; Inhoe Ku; Julia Shu-Huah Wang (Luxembourg Income Study (LIS), 2022)
Previous research has identified a distinctive East Asian model of income protection for disadvantaged children. In the wealthier East Asian societies, relative poverty rates are similar or lower than those in many Western European societies, but income transfers are low and market incomes (including private transfers) are relatively high. This chapter compares the family circumstances and household 'income packages' of disadvantaged children in Japan, Taiwan and (South) Korea with those in selected other OECD societies using data from the Luxembourg Income Study and national data sets. We look at poverty rates and the incomes of the poorest one-fifth of children in each society. In cross-national context, poverty rates are generally low in these three countries, despite low social transfers. Demographic factors (low fertility, small family size and parental age) play a significant role in this outcome - though they are also constraints in their own right. High rates of parental employment are also important.
Keywords: 330; Kinderarmut; Vergleich; Japan; Südkorea; Taiwan; OECD-Staaten